Strategi Kaur Perencanaan Dalam Meningkatkan Kualitas Pelayanan Prima Di Pemerintahan Desa Sogo Kecamatan Kedungtuban - Kastini; Oktarina, Nina (Business and Accounting Education Journal, 2025)
This research examines about the role of the Head of Planning in improving the quality of service excellence in Sogo Village, Kedungtuban Sub-district, Blora District. Using a qualitative approach and narrative design, data was collected through interviews, observation, and documentation. The findings show that the Kaur Perencanaan has the main responsibility in preparing development plans and managing village data, but is often faced with additional tasks that interfere with the focus on his main duties. Strategies implemented to improve services include developing information technology competencies, increasing human resource capacity, collaborating with other village officials, and increasing transparency and accountability. However, constraints such as limited resources and resistance to change remain a challenge. This study recommends additional staff, technology training, and the development of standard operating procedures (SOPs) to improve service effectiveness. The results of this study are expected to provide insights for the development of public service policies at the village level.